Low-temperature impact resistant high-strength bolt for high-cold railway and heat treatment method thereof
Patent Information
- Application Number
- CN202511867021.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-12-11
AI Technical Summary
[0009]针对现有高寒铁路螺栓在-60℃及以下极端环境中存在的低温冲击韧性不足、强度与硬度难以兼顾、渗层易剥落及工艺一致性差等技术缺陷,本发明旨在提供一种用于高寒铁路的耐低温冲击高强度螺栓及其热处理方法;
[0043]与现有技术相比,本发明提供的技术方案具有如下有益效果:
Smart Images

Figure CN121428496B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal materials and heat treatment technology, specifically to a low-temperature impact-resistant high-strength bolt for use in cold-weather railways and its heat treatment method. Background Technology
[0002] High-altitude railways, such as the Qinghai-Tibet Railway and the Sichuan-Tibet Railway, have extremely low temperatures, huge temperature differences, and complex geological conditions along their routes. This places stringent requirements on the performance of high-strength bolts for key connecting components. These bolts not only need to have high tensile strength to withstand huge preload and operating loads, but also must exhibit excellent impact toughness in extreme low-temperature environments of -60°C and below to prevent fatal low-temperature brittle fracture. In addition, the intense wind and sand abrasion and corrosion environment also requires the bolt surface to have high wear resistance and corrosion resistance.
[0003] Currently, the industry commonly uses alloy structural steels such as 42CrMo and 35CrMo, which undergo quenching and tempering heat treatment followed by high-temperature tempering, to manufacture high-strength bolts, or performs nitriding treatment on the bolt surface to improve wear resistance. However, existing technical solutions still have the following shortcomings when dealing with the extreme working conditions of high-altitude and cold railways:
[0004] Insufficient low-temperature impact toughness: When improving the low-temperature impact performance of 10.9 grade M36 high-strength bolts used in wind turbines, the key to improving low-temperature impact performance lies in refining grains and controlling residual elements. However, traditional quenching and tempering heat treatment processes have limited ability to refine grains and cannot completely eliminate compositional segregation within the material. These factors result in the bolt's impact energy AKv at -40℃ to -60℃ often being lower than 27J, which is far from meeting the safety requirements of high-altitude and cold-weather railways. The fundamental reason is that traditional heat treatment has a single method for controlling the microstructure and cannot effectively suppress the rapid propagation of cracks at low temperatures.
[0005] Strength, hardness, and toughness are difficult to balance. To achieve high surface hardness and wear resistance, bolts are usually nitrided. However, traditional nitriding, such as gas nitriding, has a high temperature and a clear interface between the nitrided layer and the substrate. This interface has weak bonding. Under high stress or low temperature impact, the hard and brittle nitrided layer is prone to peeling off from the substrate. On the other hand, using a high tempering temperature to ensure the toughness of the substrate will sacrifice the strength of the material. The tensile strength is usually difficult to stably exceed 1100MPa and the surface hardness, thus falling into a dilemma of strength and toughness contradiction.
[0006] Microstructure deteriorates during long-term service. Microstructure analysis of 12%Cr steel bolts that have been in long-term service at high temperatures shows that the microstructure of the material will age under long-term stress and temperature. For example, the content of δ ferrite increases, and carbides precipitate and coarsen along the grain boundaries, resulting in a decrease in the toughness and strength of the material. Although this is a high-temperature case, it reveals the serious impact of microstructure instability on performance. Although there is no high temperature in cold environments, huge alternating stress can also induce micro defects, such as dislocation entanglement, accumulation and propagation of microcracks. Traditional processes lack targeted means to stabilize and control the microstructure.
[0007] Insufficient process control precision leads to poor consistency. The manufacture of high-quality bolts heavily relies on precise control of heat treatment process parameters. However, traditional production relies on fixed process procedures and operator experience, lacking real-time feedback and adjustment capabilities. For example, during nitriding, even slight fluctuations in temperature, time, and atmosphere can lead to uneven nitrided layer thickness and unsatisfactory hardness gradient. This poor consistency results in large performance dispersion of bolts in the same batch, posing a hidden danger to railway safety operations.
[0008] In summary, existing technologies for manufacturing high-strength bolts for high-altitude and cold-weather railways suffer from several technical defects that urgently need to be addressed, including insufficient low-temperature toughness, difficulty in balancing strength and toughness, easy peeling of the diffusion layer, and poor product consistency. Therefore, there is an urgent need for a novel material design and heat treatment method that can fundamentally refine and stabilize the microstructure of the bolts, achieve a balance between ultra-high strength and ultra-high and low temperature toughness, and realize controllable and precise manufacturing processes to meet the safety and reliability requirements of critical fasteners for high-altitude and cold-weather railways. Summary of the Invention
[0009] In view of the technical defects of existing railway bolts in extreme environments of -60℃ and below, such as insufficient low-temperature impact toughness, difficulty in achieving both strength and hardness, easy peeling of the infiltration layer, and poor process consistency, this invention aims to provide a low-temperature impact resistant high-strength bolt for railways and its heat treatment method.
[0010] To achieve the above objectives, this invention employs a low-temperature impact-resistant high-strength bolt for use in cold-weather railways. The bolt body comprises, from the inside out:
[0011] The matrix has a microcrystalline grain size of ASTM grade 8.
[0012] The biomimetic nanolayers are formed on the surface of the substrate. The biomimetic nanolayers are composed of alternating deposits of TiN and VC, and the thickness of a single TiN or VC layer is less than 50 nm.
[0013] A high-entropy alloy nitriding layer is formed on the outer surface of the biomimetic nano-stack. The material system of the high-entropy alloy nitriding layer is AlCoCrFeNiTi high-entropy alloy, with a thickness greater than 50μm and a surface Vickers hardness of not less than 1200HV.
[0014] Among them, the interfacial bonding strength between the high-entropy alloy nitriding layer and the biomimetic nanolayer stack has a critical load higher than 80N as measured by the scratch method.
[0015] To achieve the above objectives, the present invention also employs a heat treatment method for preparing high-strength bolts, comprising the following steps:
[0016] S1, Pre-processing of the bolt base;
[0017] S2, biomimetic nanolayers were prepared on the pretreated bolt substrate surface by magnetron sputtering;
[0018] S3, an AlCoCrFeNiTi high-entropy alloy coating is clad onto the surface of a bolt with biomimetic nanolayers using high-speed laser cladding technology;
[0019] S4, Electromagnetically assisted salt bath nitriding treatment is performed on bolts coated with high-entropy alloy coating, wherein a pulsed electromagnetic field is applied during the nitriding process;
[0020] S5, oil quenching of bolts after nitriding treatment;
[0021] S6, Deep cryogenic vibration treatment is performed on the oil-quenched bolts;
[0022] S7, tempering treatment is performed on bolts that have undergone cryogenic vibration treatment.
[0023] Preferably, in S4, the frequency of the pulsed electromagnetic field is 1 kHz and the magnetic field strength is 5 T;
[0024] In S6, cryogenic vibration treatment refers to placing the bolt in a liquid nitrogen environment and applying ultrasonic vibrations with a frequency of 20kHz and an amplitude of 10μm.
[0025] Preferably, the pretreatment process in S1 includes a grain refinement pretreatment of the bolt matrix, the grain refinement pretreatment including:
[0026] Isothermal normalizing treatment involves heating the bolts to 950℃-980℃, holding them at that temperature for 3-5 hours, then cooling them to 720℃ at a rate of 250℃ / h, holding them at that temperature for 3-5 hours, and finally air cooling them to room temperature.
[0027] For the tempering treatment, the bolts that have undergone isothermal normalizing are heated to 700℃ and held for 2-2.5 hours; then the temperature is raised to 970℃-1000℃ and held for 0.5-1 hour; the bolts are then removed from the furnace and water-cooled to room temperature; subsequently, they are reheated to 700℃-710℃ and held for 5-8 hours, and then air-cooled to room temperature.
[0028] Preferably, in S4, the process parameters of the electromagnetic field-assisted salt bath nitriding treatment are dynamically adjusted based on a machine learning model;
[0029] The machine learning model takes as input real-time collected nitriding temperature, pulsed electromagnetic field intensity, and the nitriding layer thickness growth rate obtained through online monitoring, and outputs adjustment instructions for pulsed electromagnetic field frequency and nitriding time to control the nitriding layer thickness deviation within ±5μm.
[0030] Preferably, in S6, the ultrasonic amplitude of the cryogenic oscillation treatment is adjusted in real time by monitoring the acoustic pressure feedback signal in the liquid nitrogen medium.
[0031] When the sound pressure feedback signal is lower than the preset threshold, the ultrasonic amplitude is automatically increased to ensure that the oscillation energy is evenly distributed inside the bolt.
[0032] Preferably, after S3 and before S4, a surface condition monitoring step is added. An image acquisition device is used to acquire an image of the bolt surface after cladding. The uniformity and integrity of the coating are analyzed by an image recognition algorithm. If a defect is identified, the bolt is marked as a defective product and diverted.
[0033] Preferably, the method also performs quality control based on a three-dimensional process-microstructure-property database;
[0034] The database stores heat treatment process parameters, bolt microstructure characteristics, and final mechanical properties data in association.
[0035] Based on the database, the optimal combination of heat treatment process parameters is recommended in reverse based on the target mechanical properties using a machine learning model.
[0036] The target mechanical properties include at least an impact energy AKv greater than 55J at -60℃ and a tensile strength greater than 1200MPa.
[0037] The superior performance achieved by this invention stems from the multiple synergistic effects of structural design and composite processing technology at the microscale:
[0038] Inducing dislocation recombination, the modulus difference between TiN and VC makes the stacked interface a dislocation barrier. Dislocations accumulate at the interface and rearrange spontaneously to form low-energy dislocation walls or dislocation cell structures. These structures constitute the internal plastic buffer zone, which can absorb a large amount of energy during impact, passivate crack tips, and fundamentally improve low-temperature toughness.
[0039] To achieve biomimetic toughening, when microcracks extend to the interface, crack deflection and interlayer bridging occur, increasing the crack propagation path and consuming energy. This mechanism is consistent with the toughening principle of nacre in shells, enabling biomimetic design at the nanoscale.
[0040] To refine martensite laths, in a cryogenic environment of -196℃, the stress waves generated by ultrasonic vibration can break up the nascent martensite laths, promote nucleation, and obtain finer and more uniform submicron-sized lath bundles, while improving strength and toughness.
[0041] The process purifies and optimizes dislocations. Oscillatory energy activates pinned dislocations, promoting cross-slip and climb, reducing dislocation entanglement, and driving collaboration with biomimetic stacked dislocation cells to form a more stable three-dimensional dislocation network.
[0042] The beneficial effects of this invention are as follows:
[0043] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0044] Through a multi-synergistic toughening mechanism of fine matrix grains, biomimetic layering, and deep cryogenic oscillation, the impact energy AKv can reach more than 58J in the extreme environment of -60℃, thus solving the risk of low-temperature brittle fracture of bolts in cold railways.
[0045] The balance between high strength and high hardness, the high-entropy alloy nitriding layer and the optimized heat treatment process, enable the bolts to maintain a high tensile strength of ≥1240MPa while the surface Vickers hardness reaches 1250HV, breaking through the limitation of the contradiction between strength and toughness in traditional technology.
[0046] As an ideal intermediate transition layer, the biomimetic nanolayer forms a strong metallurgical bond with the high-entropy alloy nitriding layer. The critical load of the interface bonding reaches 85N, while that of the unconventional nitriding layer is about 40-50N, thus avoiding the problem of hard coating peeling off under impact load.
[0047] Excellent quality consistency and process controllability are achieved by dynamically controlling the nitriding process through an integrated machine learning model, with a nitriding layer thickness deviation of ≤±5μm, sound pressure feedback to optimize the energy distribution of cryogenic oscillation, and image recognition to monitor coating defects in real time. This establishes a complete intelligent quality control system, which significantly improves product qualification rate and batch stability, and solves the industry problem of poor consistency in traditional processes. Attached Figure Description
[0048] Figure 1 This is a flowchart of a heat treatment method for preparing high-strength bolts provided in Embodiment 1 of the present invention;
[0049] Figure 2 The flowchart shows the structure of the machine learning model provided in Embodiment 1 of the present invention. Detailed Implementation
[0050] To further illustrate the technical means and effects adopted by the present invention to achieve its intended purpose, exemplary embodiments will be described in detail below, examples of which are illustrated in the accompanying drawings. In the following description relating to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this application. Rather, they are merely examples of methods and systems consistent with some aspects of this application as detailed in the appended claims.
[0051] The terminology used in this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The singular forms “a,” “the,” and “the” used in this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the term “and / or” as used herein refers to and includes any or all possible combinations of one or more of the associated listed items.
[0052] The following detailed description of the specific implementation methods, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided in detail.
[0053] Example 1
[0054] Please refer to Figure 1 , 2 The bolt base is made of alloy structural steel with grade 20Cr1Mo1VTiB, and is processed into a standard hexagonal head bolt blank of M24 specification.
[0055] High-entropy alloy powder, AlCoCrFeNiTi pre-alloyed powder prepared by gas atomization method, with the following mass percentages: Al 8%, Co 20%, Cr 20%, Fe 20%, Ni 20%, Ti 12%, and powder particle size range of 15-53μm;
[0056] The magnetron sputtering target uses a composite target of Ti and VC with a purity of 99.99%.
[0057] S1. Perform grain refinement pretreatment on the bolt matrix; the specific steps are as follows:
[0058] Isothermal normalizing treatment: The bolt blank is placed in an electric resistance furnace and heated to 960℃ and held for 4 hours; then the temperature is controlled to drop to 720℃ at a cooling rate of 280℃ / h and held at 720℃ for 4 hours; finally, it is removed from the furnace and air-cooled to room temperature.
[0059] The tempering process involves heating the normalized bolts to 700℃ and holding them at that temperature for 2.5 hours; then raising the temperature to 980℃ and holding them at that temperature for 1 hour; after removing them from the furnace, quickly water-cooling them to room temperature; then immediately placing the bolts into a tempering furnace, heating them to 705℃, holding them at that temperature for 6.5 hours, and finally air-cooling them to room temperature.
[0060] S2. To prepare the biomimetic nanolayer, the pretreated bolt was placed in the vacuum chamber of a magnetron sputtering device. First, a Ti target was used to sputter for 3 minutes under an argon atmosphere of 0.8 Pa and a power of 800 W to form a TiN layer with a thickness of about 35 nm. Then, the target was switched to a VC target and sputtered for 3 minutes under the same conditions to form a VC layer with a thickness of about 40 nm. This process was repeated 20 times to finally form a TiN / VC biomimetic nanolayer with a total thickness of about 1.5 μm and an average thickness of <50 nm per layer on the surface of the bolt substrate.
[0061] S3, high-entropy alloy coating cladding, adopts a high-speed laser cladding system with the following process parameters: laser power 2800W, scanning speed 600mm / s, powder feeding rate 25g / min, and spot diameter 2mm. AlCoCrFeNiTi high-entropy alloy powder is uniformly clad onto the surface of the bolt with biomimetic nano-layers to form a dense coating with a thickness of about 150μm.
[0062] After step S3 is completed, the bolts will not immediately enter the nitriding treatment in step S4. Instead, they will go through an automated surface condition monitoring step to ensure that only bolts with qualified coating quality can enter the subsequent expensive and irreversible heat treatment process, thereby improving the overall yield and cost-effectiveness.
[0063] The image acquisition equipment uses a 5-megapixel industrial CCD camera, which is fixed in an enclosed inspection station. The camera is equipped with a ring LED light source to ensure uniform and shadowless illumination during shooting and to eliminate ambient light interference.
[0064] The image processing unit is an industrial computer equipped with Python and the OpenCV open-source computer vision library, used to run image recognition algorithms.
[0065] Decision-making and execution units, automated sorting mechanisms linked to the production line conveyor belt, such as pneumatic push rods or robotic arms;
[0066] Once the bolts are delivered to the inspection station, the process will proceed automatically as follows:
[0067] Image acquisition: The industrial camera automatically captures high-definition images of the stationary bolt surface and transmits the image data to the image processing unit in real time;
[0068] Convert the acquired color RGB images to grayscale images to simplify subsequent processing.
[0069] Using the Gaussian filtering algorithm to smooth the image effectively suppresses image noise and avoids misjudging noise points as defects;
[0070] The Canny edge detection operator is used to process the preprocessed image. The Canny edge detection operator can accurately identify areas in the image where the gray value changes drastically and delineate all possible defect boundaries, such as the outline of pores and the lines of cracks.
[0071] For the edges detected by the Canny algorithm, Hough transform is used for further analysis to identify specific shapes in the image, such as straight lines and circles, and to classify messy edge information into bright lines that are suspected cracks or circular / irregular dark spots that are suspected pores.
[0072] The algorithm performs quantitative analysis on all identified suspected defects, with the core judgment parameter being the continuous area;
[0073] Follow pre-defined, quantifiable criteria:
[0074] If the identified dark spots, i.e., pores, have a continuous pixel area that is greater than 0.1mm after conversion. 2 If so, it is determined to be a defect;
[0075] If the identified bright line, i.e. a crack, has a continuous pixel area that, after conversion, is greater than 0.1 mm. 2 If so, it is determined to be a defect;
[0076] This standard is based on a large number of process tests and can effectively filter out harmless minor surface undulations or noise, and accurately capture macroscopic defects that may affect the service life of products.
[0077] The image processing unit issues instructions to the decision execution unit based on the judgment result after marking and sorting.
[0078] In case of defective product discovery, the defective product is immediately marked in the electronic traceability record of the bolt and the automatic sorting mechanism is triggered. When the bolt reaches the fork in the road with the conveyor belt, the pneumatic push rod or the robotic arm pushes it away or grabs it to the defective product rework / scrap area.
[0079] Scenario 2 (no defect found): Good product is marked in electronic record, sorting mechanism does not move, bolt continues to flow to the next process with conveyor belt, i.e. S4 electromagnetic field assisted salt bath nitriding treatment.
[0080] In the specific production batch of this embodiment, all samples were tested by this system and no defects that would trigger diversion were found, so all of them flowed into the S4 process;
[0081] S4, electromagnetic field-assisted salt bath nitriding, the bolts are placed in a salt bath with a composition of 45% NaCNO and 35% KCl-20% Na2CO3 and treated at 570℃;
[0082] A pulsed electromagnetic field with a frequency of 1 kHz and a magnetic field strength of 5 T is applied through a coil surrounding the salt bath furnace.
[0083] The intelligent control process employs a laser thickness gauge to monitor the rate of increase in the thickness of the infiltrated layer online.
[0084] The growth rate of the nitriding layer thickness v, the nitriding temperature T, and the real-time magnetic field strength H are used as input features and fed into a regression prediction machine learning model.
[0085] Regression prediction machine learning models establish a mapping relationship from input features [T,H,v] to the predicted infiltration layer thickness Dp at a future time, such as t+Δt, i.e., Dp=f(T,H,v).
[0086] The model was pre-trained using 100 sets of historical process data. Each set of training data included the thickness growth rate v at different time points under specific process parameters (T, H) and the final measured thickness Da of the infiltration layer. Through machine learning algorithms, such as linear regression, support vector regression, or random forest, the model autonomously learned and internalized the complex nonlinear relationship between process parameters and results.
[0087] For example, when nitriding reaches the 50th minute, the current real-time data is read in: T=570℃, H=5T, v=0.95μm / min. Based on its internalized mapping relationship f, the model immediately performs calculations and predicts that if the current parameters remain unchanged, the nitriding layer thickness will reach 53μm when the total nitriding time reaches 52 minutes.
[0088] The control system compares this predicted value of 53 μm with the upper limit of the target value of 50 μm ± 5 μm of 55 μm. Although 53 μm is still within the acceptable range, in order to pursue a more accurate center value and suppress the growth trend, the control system generates an adjustment command based on the preset control strategy, such as reducing the magnetic field frequency to slightly slow down the migration rate of nitrogen atoms.
[0089] The above prediction and control process can be simplified to the following mathematical decision-making logic:
[0090]
[0091] Where f is the regression model, D target The target thickness is 50 μm in this embodiment, δ is the allowable positive deviation, which is 3 μm in this example as a control margin, and ΔH is the frequency adjustment amount, which is 0.2 kHz in this embodiment.
[0092] The control margin δ is set based on the standard deviation of the nitriding layer thickness fluctuation in production experience, and is twice the standard deviation; the frequency adjustment amount ΔH is determined through a small number of gradient tests in the early stage, which can achieve effective fine adjustment of the rate without affecting the stability of the nitriding atmosphere.
[0093] Accordingly, when the model predicts that the thickness will reach 53 μm at time t+Δt, the control law is triggered to reduce the frequency from 1 kHz to 0.8 kHz, and the control system maintains this new parameter state to continue processing.
[0094] The total nitriding time was 3 hours, and the final measured thickness of the high-entropy alloy nitrided layer was 52 μm, successfully controlling the deviation within ±5 μm.
[0095] S5, oil quenching: The nitrided bolts are quickly transferred to N32 machine oil for quenching and cooling. They are then removed after cooling to an oil temperature of about 60°C.
[0096] S6, cryogenic vibration treatment, involves rapidly transferring bolts that have been oil-quenched in S5 and whose temperature has dropped to about 60°C to the sample rack of the cryogenic vibration treatment equipment via a robotic arm or conveyor.
[0097] Ensure that the sample holder can guarantee that the bolts are evenly immersed in liquid nitrogen and maintain a fixed posture to avoid uneven ultrasonic energy transmission;
[0098] Inject liquid nitrogen into the processing chamber until the bolts are completely submerged, and monitor and ensure that the liquid nitrogen temperature is stable at -196℃;
[0099] Start the ultrasonic generator and set the initial frequency to 20kHz and the initial amplitude to 10μm;
[0100] A hydrophone, i.e. a sound pressure sensor, pre-immersed in liquid nitrogen, continuously monitors the sound pressure feedback signal generated by the propagation of ultrasound in liquid nitrogen.
[0101] The effective value of the sound pressure signal serves as a key feedback parameter, and its stability and intensity directly reflect the efficiency and uniformity of ultrasonic energy transmission within the medium and bolt.
[0102] In this embodiment, the preset threshold for the sound pressure feedback signal is set to 0.5 atmospheres, which can be adjusted according to actual experimental data.
[0103] The preset threshold of 0.5 atmospheres is mainly based on a comprehensive consideration of energy coupling efficiency and the critical point of cavitation effect. In liquid nitrogen, a stable sound pressure signal directly reflects the efficiency of ultrasonic energy transmission into the bolt.
[0104] In practical applications, if the sound pressure value is consistently below 0.3 atmospheres, it indicates that the ultrasonic energy has been excessively attenuated in liquid nitrogen before reaching the bolt surface, making it impossible to achieve effective grain refinement and dislocation reorganization.
[0105] If the sound pressure value exceeds 0.7 atmospheres, it is easy to trigger a violent cavitation effect near the bolt surface. The large number of bubbles generated will block the energy transmission and may cause impact damage to the precision biomimetic nanolayers.
[0106] The preset threshold is best set between 0.3 and 0.7 atmospheres. Setting the threshold at the midpoint of the range, 0.5 atmospheres, can provide sufficient buffer space for the control system, ensuring that the processing is both effective and safe.
[0107] The control system compares the sound pressure signal monitored in real time by the hydrophone with a preset threshold:
[0108] When the real-time sound pressure feedback signal is below 0.5 atmospheres, it is determined that the current ultrasonic energy coupling is insufficient. This may be due to liquid nitrogen film adhesion or slight changes in bolt position, which leads to a decrease in energy transfer efficiency. At this time, the control system will automatically increase the ultrasonic amplitude, for example, from 10μm to 12μm, to enhance energy output and restore effective oscillation processing.
[0109] After adjustment, the system continues to monitor the sound pressure feedback. When the sound pressure signal recovers and stabilizes above the preset threshold for 2 minutes, the control system automatically restores the ultrasonic amplitude to the initial 10μm to maintain stable processing and prevent overprocessing.
[0110] This monitoring-comparison-adjustment process is performed in a closed loop, automatically, and in real time throughout the entire processing cycle.
[0111] The total cryogenic vibration treatment time was set to 60 minutes, starting from the start of the ultrasonic wave, to ensure that the bolts received sufficient microstructure control at ultra-low temperatures.
[0112] After the predetermined processing time is reached, the system automatically shuts down the ultrasonic generator;
[0113] The bolts are removed from the liquid nitrogen in preparation for the next S7 tempering process.
[0114] S7, tempering treatment: the bolts are placed in a tempering furnace, heated to 300°C, and held for 2 hours to relieve stress. Finally, they are air-cooled to room temperature to obtain the finished bolts.
[0115] The interfacial bonding strength was determined using a CETR-UMT-3 scratch tester according to ASTM C1624-20 standard. The critical load was determined by the abrupt change in acoustic emission. A diamond indenter with a radius of 100 μm was used, and the test was conducted at a loading rate of 10 N / min. The critical load for interfacial bonding between the high-entropy alloy nitrided layer and the biomimetic nanolayer was determined to be 85 N by the abrupt change in the acoustic emission signal and friction force curve.
[0116] The surface Vickers hardness was measured using a 402MVD Vickers hardness tester under a test force of 200gf, and the surface hardness of the bolt was found to be 1250HV.
[0117] Low-temperature impact toughness was tested by machining bolts into standard Charpy V-notch impact specimens, keeping them in a -60℃ low-temperature chamber, and measuring the impact energy AKv=58J.
[0118] The tensile strength of the full-size bolts was tested using a universal tensile testing machine and found to be 1240 MPa.
[0119] Metallographic examination was conducted according to the national standard GB / T 6394-2017 "Method for Determination of Average Grain Size of Metals". Samples were prepared from the cross-section of the finished bolts. After grinding and polishing, the samples were etched with a 4% nitric acid alcohol solution. The samples were observed and evaluated under a metallographic microscope using a comparative method. Five fields of view were randomly selected at the center of the bolt shank for evaluation. The average grain size level reached ASTM 8 or finer, with the specific evaluation result being ASTM 8.5. This refined grain structure is one of the core reasons why the bolts achieve high strength and excellent low-temperature impact toughness.
[0120] All process parameters of this embodiment, such as normalizing at 960℃ / 4h, nitriding at 570℃ / 3h, the obtained microstructure characteristics, such as grain size of 8.5 grade, nitriding layer thickness of 52μm, and the final mechanical property data, such as AKv=58J, tensile strength of 1240MPa, critical load of 85N, and hardness of 1250HV, are stored as a complete record in the process-structure-property three-dimensional map database.
[0121] Specifically, the performance achieved in this embodiment (impact energy AKv = 58J at -60℃, tensile strength = 1240MPa) has been stored in the database as a set of compliance data. The database is used to recommend the optimal combination of heat treatment process parameters for new performance targets, requiring an impact energy AKv greater than 55J and a tensile strength greater than 1200MPa at -60℃.
[0122] Example 2
[0123] Similar to Example 1, an M24 bolt blank made of 20Cr1Mo1VTiB steel and AlCoCrFeNiTi high-entropy alloy powder of the same composition were used.
[0124] Pre-treatment of the bolt matrix to refine grain size:
[0125] Isothermal normalizing treatment involves heating the bolt blank to 950℃ and holding it at that temperature for 5 hours; then cooling it down to 720℃ at a controlled rate of 250℃ / h and holding it at 720℃ for 5 hours; finally, removing it from the furnace and air-cooling it to room temperature.
[0126] The tempering process involves heating the normalized bolts to 690°C and holding them for 2 hours; then raising the temperature to 1000°C and holding them for 0.5 hours; after removing them from the furnace, quickly water-cooling them to room temperature; then immediately placing the bolts into a tempering furnace, heating them to 710°C, holding them for 5 hours, and finally air-cooling them to room temperature.
[0127] S2, prepare biomimetic nanolayers, the process is exactly the same as in Example 1, ensuring that the thickness of a single layer of the biomimetic nanolayers is <50nm;
[0128] S3, High-entropy alloy coating cladding: The process is the same as in Example 1;
[0129] Surface condition monitoring was conducted using the same image recognition system and judgment criteria as in Example 1, and all samples in this batch passed the test.
[0130] S4, electromagnetic field-assisted salt bath nitriding, involves placing the bolts in a salt bath of the same composition and treating them at 560°C;
[0131] Apply a pulsed electromagnetic field: initial frequency 1kHz, magnetic field strength 5T;
[0132] In the intelligent control process, when the nitriding process reached 90 minutes, the model predicted based on real-time data that the nitrided layer thickness would be 48 μm when the total time reached 2.5 hours. To get closer to the target center value, the model output a command to fine-tune the frequency of the pulsed electromagnetic field to 0.9 kHz. The total nitriding time was 2.5 hours, and the final measured thickness of the high-entropy alloy nitrided layer was 49 μm.
[0133] S5, oil quenching is the same as in Example 1;
[0134] S6, cryogenic oscillation treatment, the process parameters and sound pressure feedback control logic are exactly the same as in Example 1, the total time is 60 minutes;
[0135] S7, tempering treatment: put the bolts into a tempering furnace, heat to 280°C (20°C lower than in Example 1), hold for 2 hours, and finally air cool to room temperature.
[0136] The finished bolts were subjected to the same standardized tests as in Example 1:
[0137] Low-temperature impact toughness, with an impact energy of AKv = 56J measured at -60℃;
[0138] Tensile strength: The measured tensile strength of the full-size bolts was 1210 MPa;
[0139] The interface bonding strength was determined by a scratch test, which showed a critical load of 78 N.
[0140] The surface Vickers hardness was measured to be 1180 HV.
[0141] Metallographic examination revealed that the average grain size of the matrix was ASTM 8.0.
[0142] All process parameters, microstructure characteristics and final mechanical property data of this embodiment are stored as a new record, different from that of Embodiment 1, in the process-structure-property three-dimensional map database.
[0143] This embodiment also achieved the set target mechanical properties (AKv>55J at -60℃, tensile strength>1200MPa). Even with adjustments to key process parameters, this invention can still stably produce qualified products.
[0144] Comparative Example 1
[0145] The same 20Cr1Mo1VTiB steel M24 bolt blank as in Example 1;
[0146] S2, biomimetic nanolayer fabrication and S3, high-entropy alloy cladding are omitted;
[0147] For bolts subjected to conventional gas nitriding at 520℃ for 8 hours, the ammonia decomposition rate is 30%-35%.
[0148] After nitriding, conventional oil quenching and low-temperature tempering at 180°C are performed to maintain the hardness of the nitrided layer, but this is different from the high-temperature tempering in Example 1.
[0149] No cryogenic oscillation treatment is performed, no pulsed electromagnetic field is applied, and no intelligent control model is used;
[0150] This comparative example represents the conventional nitriding + low-temperature tempering process used in existing technologies to achieve surface hardness;
[0151] The finished bolts from Examples 1, 2, and 1 were subjected to standardized performance tests, and the results are summarized in the table below:
[0152] Table 1 Comparison of performance test results between the examples and the comparative examples
[0153] Performance indicators Example 1 Example 2 Comparative Example 1 Test Standards / Remarks Grain size (ASTM grade) 8.5 8 5 GB / T 6394-2017 Impact energy AKv (J) at -60℃ 58 56 19 GB / T 229-2020, Examples 1 and 2 both >55J Tensile strength (MPa) 1240 1210 980 GB / T 3098.1-2010, Examples 1 and 2 both >1200MPa Surface hardness (HV) 1250 1180 950 Load 200gf Infiltration layer thickness (μm) 52 49 25 Metallographic measurement Uniformity of infiltration layer Thickness deviation ±3μm Thickness deviation ±4μm Thickness deviation ±15μm Standard deviations were measured and calculated at different locations on the bolt; in Examples 1 and 2, the deviations were < ±5 μm. Interface bonding critical load (N) 85 78 42 The scratch test demonstrates that the biomimetic stacked structure and the high-entropy alloy nitriding layer are crucial to the bonding strength. Salt spray test (h) >1000 No red rust >1000 No red rust 200 showed red rust GB / T 10125-2021, High-entropy alloy nitriding provides excellent corrosion resistance.
[0154] The impact energy at -60℃ of Comparative Example 1 is only 19J, which poses a risk of low-temperature brittle fracture.
[0155] The impact energy of Embodiments 1 and 2 of the present invention reached 58J and 56J respectively, with an improvement of more than 190%, which fully meets the requirements of high-altitude railways for the low-temperature toughness of bolts. This is mainly due to the synergistic effect of multiple technologies such as matrix fine grain pretreatment, ASTM grade 8 or above, biomimetic nano-layer induced favorable microstructure, and deep cryogenic vibration treatment to further refine martensite and release stress.
[0156] Comparative Example 1, due to its low tempering temperature, ensured a surface hardness of 950 HV, but its poor matrix toughness resulted in a tensile strength of 980 MPa that could not exceed 1000 MPa.
[0157] This invention achieves an ultra-high surface hardness (>1180HV) and a tensile strength (above 1200MPa) through optimized tempering process and composite strengthening, thus resolving the contradiction between high hardness and high strength in traditional technologies.
[0158] The conventional nitrided layer in Comparative Example 1 is thin, uneven, and has weak adhesion to the substrate, with a critical load of 42N, and is easily peeled off.
[0159] The electromagnetic field-assisted nitriding of this invention increases the thickness and uniformity of the nitriding layer. The biomimetic nano-layer serves as an ideal intermediate layer, forming an interface bond with the high-entropy alloy nitriding layer, thus preventing the coating / nitriding layer from peeling off and failing under impact loads.
[0160] The dense and chemically stable AlCoCrFeNiTi high-entropy alloy nitriding layer provides corrosion protection against corrosion damage, unlike conventional nitriding layers.
[0161] Although alternative embodiments of this application have been described, those skilled in the art, upon learning the basic inventive concept, can make further changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this application.
[0162] The above specific embodiments further illustrate the purpose, technical solution and beneficial effects of this application. It should be understood that the above are only specific embodiments of this application and are not intended to limit the scope of protection of this application. Any modifications, equivalent substitutions, improvements, etc., made on the basis of the technical solution of this application should be included within the scope of protection of this invention.
Claims
1. A heat treatment method for high-strength bolts, characterized in that, Includes the following steps: S1, Pre-processing of the bolt base; S2, biomimetic nanolayers were prepared on the pretreated bolt substrate surface by magnetron sputtering; S3, On the surface of the bolt with the biomimetic nanolayer, an AlCoCrFeNiTi high-entropy alloy coating is clad by high-speed laser cladding technology; S4, Electromagnetically assisted salt bath nitriding treatment is performed on bolts coated with high-entropy alloy coating, wherein a pulsed electromagnetic field is applied during the nitriding process; S5, oil quenching of bolts after nitriding treatment; S6, Deep cryogenic vibration treatment is performed on the oil-quenched bolts; S7, Tempering treatment is performed on bolts that have undergone cryogenic shock treatment; In S6, the cryogenic vibration treatment refers to placing the bolt in a liquid nitrogen environment and applying ultrasonic vibration with a frequency of 20kHz and an amplitude of 10μm. The biomimetic nanolayers are formed on the surface of the substrate and are composed of alternating deposits of TiN and VC, with the thickness of a single TiN or VC layer being less than 50 nm.
2. The heat treatment method according to claim 1, characterized in that, In S4, the frequency of the pulsed electromagnetic field is 1 kHz and the magnetic field strength is 5 T.
3. The heat treatment method according to claim 1, characterized in that, The pretreatment process in S1 includes a grain refinement pretreatment of the bolt matrix, wherein the grain refinement pretreatment includes: Isothermal normalizing treatment involves heating the bolts to 950℃-980℃, holding them at that temperature for 3-5 hours, then cooling them to 720℃ at a rate of 250℃ / h, holding them at that temperature for 3-5 hours, and finally air cooling them to room temperature. For the tempering treatment, the bolts that have undergone isothermal normalizing are heated to 700℃ and held for 2-2.5 hours; then the temperature is raised to 970℃-1000℃ and held for 0.5-1 hour; the bolts are then removed from the furnace and water-cooled to room temperature; subsequently, they are reheated to 700℃-710℃ and held for 5-8 hours, and then air-cooled to room temperature.
4. The heat treatment method according to claim 1, characterized in that, In step S4, the process parameters of the electromagnetic field-assisted salt bath nitriding treatment are dynamically adjusted based on a machine learning model. The machine learning model takes as input real-time collected nitriding temperature, pulsed electromagnetic field intensity, and the nitriding layer thickness growth rate obtained through online monitoring, and outputs adjustment commands for pulsed electromagnetic field frequency and nitriding time to control the nitriding layer thickness deviation within ±5μm.
5. The heat treatment method according to claim 1, characterized in that, In step S6, the ultrasonic amplitude of the cryogenic oscillation treatment is adjusted in real time by monitoring the acoustic pressure feedback signal in the liquid nitrogen medium. When the sound pressure feedback signal is lower than a preset threshold, the ultrasonic amplitude is automatically increased to ensure that the oscillation energy is evenly distributed inside the bolt.
6. The heat treatment method according to claim 1, characterized in that, After S3 and before S4, a surface condition monitoring step is added. An image acquisition device is used to acquire an image of the bolt surface after cladding. The uniformity and integrity of the coating are analyzed by an image recognition algorithm. If a defect is identified, the bolt is marked as a defective product and diverted.
7. The heat treatment method according to claim 1, characterized in that, The method also performs quality control based on a three-dimensional process-microstructure-property database. The database is associated with and stores heat treatment process parameters, bolt microstructure characteristics, and final mechanical property data. Based on the database, the optimal combination of heat treatment process parameters is recommended in reverse based on the target mechanical properties using a machine learning model. The target mechanical properties include at least an impact energy AKv greater than 55J at -60℃ and a tensile strength greater than 1200MPa.
8. A low-temperature impact-resistant high-strength bolt for use in cold-weather railways, based on the heat treatment method of the high-strength bolt according to any one of claims 1-7, characterized in that... The bolt body includes, from the inside out, the following components: The matrix has a microcrystalline grain size of ASTM grade 8. A biomimetic nanolayer is formed on the surface of the substrate. The biomimetic nanolayer is composed of alternating deposits of TiN and VC, and the thickness of a single TiN or VC layer is less than 50 nm. A high-entropy alloy nitriding layer is formed on the outer surface of the biomimetic nano-stack. The material system of the high-entropy alloy nitriding layer is AlCoCrFeNiTi high-entropy alloy, with a thickness greater than 50μm and a surface Vickers hardness of not less than 1200HV. The interfacial bonding strength between the high-entropy alloy nitriding layer and the biomimetic nanolayer is higher than 80N, as measured by the scratch method.
Citation Information
Patent Citations
Gradient transition layer for improving film-substrate bonding strength of high-entropy nitride film and preparation method
CN114540753A
Film formation method, and member coated with hard coating film
JP2012158793A